2016
DOI: 10.1111/cod.12711
|View full text |Cite
|
Sign up to set email alerts
|

Contact sensitization in Dutch children and adolescents with and without atopic dermatitis – a retrospective analysis

Abstract: Sensitization prevalences in children with and without atopic dermatitis were similar, but children with atopic dermatitis reacted significantly more often to lanolin alcohol and fragrances. Testing with additional series besides the European baseline series may be necessary, as reactions to, for example, cocamidopropyl betaine and Amerchol L-101 may otherwise be missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
67
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 53 publications
15
67
3
Order By: Relevance
“…In the current study, we found a sensitization rate of 71% ( n = 24/34) in children and 86% ( n = 12/14) in adults amongst 48 difficult‐to‐treat AD patients. This prevalence in children is much higher than in the previously mentioned study by Lubbes et al 21. and exceeds the prevalence of 30% in AD children and adolescents reported by Simonsen et al 34.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…In the current study, we found a sensitization rate of 71% ( n = 24/34) in children and 86% ( n = 12/14) in adults amongst 48 difficult‐to‐treat AD patients. This prevalence in children is much higher than in the previously mentioned study by Lubbes et al 21. and exceeds the prevalence of 30% in AD children and adolescents reported by Simonsen et al 34.…”
Section: Discussioncontrasting
confidence: 58%
“…The group composition of the population under study is dominated by children, with only a quarter of patients having reached adult age. A recent large study conducted in three University Hospitals in The Netherlands, including our centre, showed that 48% of children with AD who were tested based on clinical suspicion had one or more positive patch test reactions compared to 47% of children without AD 21. In the current study, we found a sensitization rate of 71% ( n = 24/34) in children and 86% ( n = 12/14) in adults amongst 48 difficult‐to‐treat AD patients.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…involving repeated open application or provocative use testing with lanolin alcohol‐containing products, to ascertain clinical relevance of a positive patch test reaction. Recently, it has been pointed out that in children and adolescents with atopic eczema, also the lanolin alcohol derivative Amerchol L101 (which has no own INCI name) commonly caused positive patch test reactions . Therefore, it may be worthwhile to further examine the most suitable patch test preparation.…”
Section: Discussionmentioning
confidence: 99%